2016
DOI: 10.7717/peerj.1734
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling potential virulence factor candidates inXanthomonas citri. subsp.citriby secretome analysis

Abstract: Citrus canker is a major disease affecting citrus production in Brazil. It’s mainly caused by Xanthomonas citri subsp. citri strain 306 pathotype A (Xac). We analysed the differential expression of proteins secreted by wild type Xac and an asymptomatic mutant for hrpB4 (ΔhrpB4) grown in Nutrient Broth (NB) and a medium mimicking growth conditions in the plant (XAM1). This allowed the identification of 55 secreted proteins, of which 37 were secreted by both strains when cultured in XAM1. In this secreted protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 92 publications
0
23
0
Order By: Relevance
“…The type II secreted proteins are well-characterized in Xanthomonas spp. [ 62 , 63 , 64 ], and many of these proteins are cell wall-degrading enzymes that contribute to bacterial virulence, translocate virulence factors into the plant cells, and facilitate the acquisition of nutrients [ 65 , 66 ]. In addition to type II effectors, Xaj also employs type III effectors, some of which were detected in infected tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The type II secreted proteins are well-characterized in Xanthomonas spp. [ 62 , 63 , 64 ], and many of these proteins are cell wall-degrading enzymes that contribute to bacterial virulence, translocate virulence factors into the plant cells, and facilitate the acquisition of nutrients [ 65 , 66 ]. In addition to type II effectors, Xaj also employs type III effectors, some of which were detected in infected tissues.…”
Section: Discussionmentioning
confidence: 99%
“…By fusion with GFP, we did found that most of XAC1347 protein is bonded to cell membrane ( Supplementary Figure S4A ). As a biotrophic pathogen, Xcc penetrates the apoplast and releases a large number of molecules into the apoplastic space, some of which are pathogen-associated molecular patterns (PAMPs), such as lipopolysaccharides, flagellin or elongation factor Tu ( Facincani et al, 2014 ; Ferreira et al, 2016 ; Carnielli et al, 2017 ). The western blot results indicated that the XAC1347-C-Myc protein was detected from the total cell extract, but not present in the culture supernatant ( Supplementary Figure S4B ).…”
Section: Discussionmentioning
confidence: 99%
“…An oprB mutant is impaired in biofilm formation, adherence to the host, and virulence ( Ficarra et al, 2017 ). Through proteomics and transposon-based analysis, a large number of outer membrane proteins, transporters and membrane-bound receptors have been identified to be associated with Xcc infection ( Yan and Wang, 2012 ; Facincani et al, 2014 ; Song et al, 2015 ; Ferreira et al, 2016 ; Carnielli et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar in silico studies have been conducted on various pathogenic genomes and proteomes to identify the repertoire of SASPs which represented novel candidates as virulence factors. These include: Taenia solium ( Gomez et al, 2015 ), Phytophthora infestans ( Raffaele et al, 2010 ), Yersinia pestis ( Yen et al, 2007 ), Xanthomonas citri ( Ferreira et al, 2016 ), Coxiella burnetii ( Ferreira et al, 2016 ), and enteric pathogens including Shigella spp, E. coli , Vibrio cholerae , Yersinia enterocolitica ( Hashmi et al, 2010 ), Salmonella spp. , and Anaplasma marginale ( Palmer et al, 2012 ).…”
Section: Application Of Proteome-scale In Silico Smentioning
confidence: 99%